Analysis of Modern Anti-Virus Software in Cyber Security Tasks - Astakhov, D. S; Lysenko, N. O; Mazurenko, V. B; Fedorovych, A. I. (Science and Transport Progress, 2021)
Purpose. The research is aimed at gaining general knowledge about modern anti-virus software. Because it is one aspect of cybersecurity, and is subject to ongoing discussions about its appropriateness. Methodology. To obtain data, the authors conducted a review of world literature on the topic of work using full-text and abstract databases. Signature and heuristic methods of antivirus software operation are considered. As well as the conditional division of these products into programs-detectors, programs-doctors, programs-auditors, programs-filters, programs-immunizers was made. Findings. Content analysis of publications in the direction of anti-virus software proves the number of aspects studied. The question of the ability of such software not only to recognize the threat, but also to be able to destroy it is being studied. To perform this task, the antivirus must have the following functions: regular (or real-time) scanning of system files and programs; scanning the content of messengers and e-mail; full computer scan at the user’s command; monitoring of incoming and outgoing network traffic; elimination of the malware operation consequences. In addition, a comparative analysis of the most popular anti-virus software makes it possible to identify the disadvantages and advantages of each of them. Originality. Systematic and generalized analysis of the existing and most common anti-virus software has been further developed, which allows ordinary users to make informed choices about installing such software packages. Practical value. Based on the results obtained, it is possible to adjust your own actions regarding safe work on the Internet. In addition, the article aims to dispel myths suggesting that users do not protect their computers from malware at all. These studies can also be useful in studying the discipline "Fundamentals of Software Testing", the organization of scientific and practical seminars, refresher courses and etc.